Whither globalization? : the vortex of knowledge and ideology - Mittelman, James H. (Rethinking globalizations, 2004)
Globalization is usually said to be about markets and power, and, as a byproduct, culture. Whither Globalization? goes further, arguing that globalization may also be understood as a way of knowing and representing the world.